Novel Insights on Nutrient Management of Sarcopenia in Elderly. (29th January 2015) - Rondanelli, Mariangela; Faliva, Milena; Monteferrario, Francesca; Peroni, Gabriella; Repaci, Erica; Allieri, Francesca; Perna, Simone
Abstract : Sarcopenia is defined as a syndrome characterized by progressive and generalized loss of muscle mass and strength. The more rationale approach to delay the progression of sarcopenia is based on the combination of proper nutrition, possibly associated with the use of dietary supplements and a regular exercise program. We performed a narrative literature review to evaluate the till-now evidence regarding (1) the metabolic and nutritional correlates of sarcopenia; (2) the optimum diet therapy for the treatment of these abnormalities. This review included 67 eligible studies. In addition to the well recognized link between adequate intake of proteins/amino acids and sarcopenia, the recent literature underlines that in sarcopenic elderly subjects there is an unbalance in vitamin D synthesis and in omega-6/omega-3 PUFA ratio. Given the detrimental effect of these metabolic abnormalities, a change in the lifestyle must be the cornerstone in the treatment of sarcopenia. The optimum diet therapy for the sarcopenia treatment must aim at achieving specific metabolic goals, which must be reached through accession of the elderly to specific personalized dietary program aimed at achieving and/or maintaining muscle mass; increasing their intake of fish (4 times/week) or taking omega-3 PUFA supplements; taking vitamin D supplementation, if there are low serum levels.